Emotional perception: Correspondence of early and late event-related potentials with cortical and subcortical functional MRI - Sabatinelli, Dean; Keil, Andreas; Frank, David W.; Lang, Peter J. (Biological psychology, 2013)
► Emotional modulation of the LPP correlates strongly with sub and visual cortical signal. ► Emotional modulation of the EPN correlates with sub, but not visual cortical signal. ► The slow-wave LPP reflects an aggregate of emotional discrimination processes. This research examines the relationship between brain activity recorded with functional magnetic resonance imaging (fMRI) and event related potentials (ERP) as these responses varied over a series of emotionally evocative and neutral pictures. We investigate the relationship of early occipitotemporal and later centroparietal emotion-modulated ERPs in one sample to fMRI estimates of neural activity in another sample in a replicated experiment. Using this approach, we aimed to link effects found in time-resolved electrocortical measures to specific neural structures across individual emotional and nonemotional picture stimuli. The centroparietal late positive potential (LPP) showed covariation with emotion-modulated regions of hemodynamic activation across multiple dorsal and ventral visual cortical structures, while the early occipitotemporal potential was not reliably associated. Subcortical and corticolimbic structures involved in the perception of motivationally relevant stimuli also related to modulation of the LPP, and were modestly associated to the amplitude of the early occipitotemporal potential. These data suggest that early occipitotemporal potentials may reflect multiple sources of modulation including motivational relevance, and supports the perspective that the slow-wave LPP represents aggregate cortical and subcortical structures involved in emotional discrimination.